Analysis of weather elements based on measurement results of Automated Weather System (AWS) type Vaisala MAWS 201 - Muhammad Ihsan Qudratullah; Asrizal Asrizal; Zulhendri Kamus (PILLAR OF PHYSICS, 2017)
Human activities due influenced by natural conditions and natural conditions are affected by human activities. This phenomenon is interesting because everybody couldn't control over the weather. Accuracy weather information can minimize the negative effects of weather such as aircraft accidents, material losses due to flooding and other. AWS is instrument used to measure the weather elements. However, in practice most of the weather forecast is only used to help smooth plane flight, and the result can only be accessed by certain institutions. In fact, if viewed more deeply the weather forecast has many benefits in human activities. This research objective is to determine the characteristics of the weather elements  that can be utilized for various fields of human life. This research was descriptive which describe the AWS Vaisla MAWS 201 and the elements of the weather based on measurements using Vaisala MAWS 201. AWS measurement data retrieval was done directly by observing changes in weather elements occurring on the computer display. The computer display of measurement data elements of weather can be downloaded to be processed as information material. From these research activities could be offered two results. First AWS consist of remote terminal Unite (RTU), personal computer (CP), Sensors. AWS can measure some weather elements at once. Second, the measurement data obtained from the results that the average temperature in 2013 and 2014 was 250C -300C and minimum temperature of 240C. For the measurement of rainfall average per year is 35 mm and 0 mm. The air pressure value of the average per year is 1012 mb and 1009 mb. Air humidity is 80 and 82. Wind speed is taken from an annual average value of 10 m / s in 2014 and 3 m / s in 2013